Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: • The Impact of Transformational Leadership Styles on the Job Performance of Cycle Two School Teachers in Muscat Governorate, Sultanate of Oman: An Analytical Study Ms. Amal Saif Al-Humaidi • The role of governments in promoting the transition to a knowledge economy and the challenges they face Ms. Wafiah Othman Alsubhi, Ms. Maha Saleh Saad Alyahyan • The Role of Prophetic Guidance in Promoting Sustainable Peace Values Co-Prof. Fari’a Abdullah Ghotish Al-Khuza’i, Prof. Hanadi Eisa Mohana Ibrahim • The Level of Awareness of Kindergarten Teachers at Baghdad Al-Karkh Second Education Directorate of the Importance of Digital Education Asst-Prof. Ola Hussein Alwan • Marital compatibility among female teachers in Hail City Mrs. Alaa Falah F. Al-Hamdhawi • Persuasive Intelligence and Its Relationship to Mindfulness Among Kindergarten Teachers Lecturer Hind Luay Abdulhameed • The Impact of Relative Contribution of Psychological Capital and Academic Inclusion in Predicting the Quality of Life among Female University Students in Saudi Arabia Dr. Norah Abdulrahman Almotrefi